Documentation & Digital vol. 2 (diségno, 2019)
As reported in the preface of Massimiliano Lo Turco to this collection of researches, the awakening of a “Sleeping Beauty” can be considered as the main topic of this book. “Sleeping Beauty “is a name that comes from a project promoted by the Italian Ministry of Cultural Heritage, regarding a classification work aimed at civic museums, with the ambition of setting up a database of an important selection of works that do not find space in the exhibition areas accessible to the public. (read more)